Melt Segregation in Deep Crustal Hot Zones: a Mechanism for Chemical Differentiation, Crustal Assimilation and the Formation of Evolved Magmas - Solano,JMS; Jackson,MD; Sparks,RSJ; Blundy,JD; Annen,C (Journal of Petrology, 2012)
Mantle-derived basaltic sills emplaced in the lower crust provide amechanism for the generation of evolved magmas in deep crustal hotzones (DCHZ).This study uses numerical modelling to characterizethe time required for evolved magma formation, the depth and temperatureat which magma formation occurs, and the composition ofthe magma.The lower crust is assumed to comprise amphibolite. Inan extension of previous DCHZ models, the new model couples heattransfer during the repetitive emplacement of sills with mass transfervia buoyancy-driven melt segregation along grain boundaries.The resultsshed light on the dynamics of DCHZ development and evolution.TheDCHZ comprises a mush of crystals plus interstitial melt,except when a new influx of basaltic magma yields a short-lived(20^200 years) reservoir of melt plus suspended crystals (magma).Melt segregation and accumulation within the mush yields two contrastingmodes of evolved magma formation, which operate over timescalesof c. 10 kyr-1 Myr, depending upon emplacement rate andstyle. In one, favoured by emplacement via over-accretion, or emplacementat high rates, evolved magma forms in the crust overlying theintruded basalt sills, and is composed of crustal partial melt, and residualmelt that has migrated upwards out of the crystallizingbasalt. In the other, favoured by emplacement via under- orintra-accretion, or by emplacement at lower rates, evolved magmaforms in the intruded basalt, and the resulting magma is composedprimarily of residual melt. In all cases, the upward migration ofbuoyant melt yields cooler and more evolved magmas, which arebroadly granitic in composition. Chemical differentiation is thereforedriven by melt migration, because the melt migrates through, andchemically equilibrates with, partially molten rock at progressivelylower temperatures. Crustal assimilation occurs during partial melting,and mixing of crustal and residual melt occurs when residualmelt migrates into the partially molten crust, yielding